2016
DOI: 10.1111/anu.12392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soy protein ratio, lipid content and minimum level of krill meal in plant-based diets over the growth and digestibility of the white shrimp,Litopenaeus vannamei

Abstract: This study evaluated the effects of soy protein ratio, lipid content and the minimum dietary level of krill meal in plant-based diets over the growth performance and digestibility of Litopenaeus vannamei. Nine plant-based diets varied the soybean meal (SBM) and soy protein concentrate (SPC) inclusion ratio at 1 : 2.3, 1 : 1 and 2.5 : 1, and their dietary lipid content at 121.4 AE 9.4, 102.3 AE 1.2, and 79.9 AE 1.2 g kg À1 (in a dry matter basis). An additional diet containing 120 g kg À1 of fish meal (salmon b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…The diet with 3% KRM remained the most effective in the increase of shrimp final BW and yield and in the reduction of FCR in L. vannamei . The ability of KRM in stimulating feed ingestion and growth performance in penaeid shrimp is corroborated by other studies conducted with both P. monodon and L. vannamei (Sá et al, ; Sabry‐Neto et al, ; Smith et al, ; Williams et al, ). However, there was scarce information with regard to its performance relative to other marine raw materials with stimulatory feeding properties.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The diet with 3% KRM remained the most effective in the increase of shrimp final BW and yield and in the reduction of FCR in L. vannamei . The ability of KRM in stimulating feed ingestion and growth performance in penaeid shrimp is corroborated by other studies conducted with both P. monodon and L. vannamei (Sá et al, ; Sabry‐Neto et al, ; Smith et al, ; Williams et al, ). However, there was scarce information with regard to its performance relative to other marine raw materials with stimulatory feeding properties.…”
Section: Discussionsupporting
confidence: 68%
“…In recent years, there has been a strong movement toward low fishmeal shrimp feeds (Tacon & Metian, ), resulting in a greater dietary inclusion of plant and rendered animal by‐products (Malcorps et al, ; Suresh, Paramasivam, Vasagam, & Nates, ). Such changes can severely impact shrimp growth, as these alternate proteins are often deficient in one or more essential nutrients (Nunes, Sá, Browdy, & Vázquez‐Añón, ; Sá, Sabry‐Neto, Cordeiro‐Júnior, & Nunes, ) and contain antinutritional factors, which can suppress feeding stimulus and reduce nutrient bioavailability (Gatlin et al, ; Nunes, Sá, Andriola‐Neto, & Lemos, ; Sabry‐Neto, Lemos, Raggi, & Nunes, ).…”
Section: Introductionmentioning
confidence: 99%
“…Shrimp of 0.65 ± 0.28 g body weight (n = 152) were transferred and stocked in 50 clear-water indoor tanks of 0.5 m 3 at 80 shrimp per tank (140 shrimp/m²) under a water salinity of 31 ± 1.8 g/L. The tank rearing system adopted is described by Sabry-Neto, Lemos, Raggi, and Nunes (2016).…”
Section: Growth Studymentioning
confidence: 99%
“…Several studies have shown that the whiteleg shrimp, Litopenaeus vannamei, can be raised with almost complete replacement of fishmeal (FM) by plant proteins, mainly soybean meal and concentrate (Suárez et al, 2009;Sookying, Davis & Soller Dias da Silva, 2013;Sabry-Neto et al, 2016). However, industrially compounded feeds continue to rely on FM as a significant source of dietary protein.…”
Section: Introductionmentioning
confidence: 99%